TEMPERATURE MEASUREMENTS IN THE VELIKAN GEYSER BASIN (VALLEY OF GEYSERS, KAMCHATKA) - Droznin V.A.; Bakhtiyarov V.F.; Levin V.E. (My University, 1999)
Based on the temperatures measured in the Velikan Geyser basin using a recording system manufactured at the Institute of Volcanology, the mechanism of the geyser operation is discussed to explain the irregularity of its eruptions. It is shown that the behavior of the geyser approximates a water well model.